The role of self breath-testing devices in the Kimberley region of Western Australia - Cercarelli, Rina; Mak, Donna; Mills, K.; Jefferies, B. (Australian Health Promotion Association, 2004)
Issue addressed: To examine the role that alcohol breath-testing devices in licensed premises may have in rural and remote areas of Australia. Methods: Data to monitor the use of the wall-mounted, alcohol breath-testing devices were collected by download from the devices themselves and through survey tools for bar staff and the patrons of licensed premises. A total of 488 patrons of licensed premises were interviewed for the pre-intervention data collection and 952 patrons were interviewed post-intervention. Hand-held devices were used by 434 people at large social gatherings and all of these completed a questionnaire. Eighty-three bar staff were interviewed over the course of the project and 54 observations were made of their serving practices. A total of 695 observations of the methods of transport used by patrons leaving licensed premises were made pre- intervention and 1,095 were made post-intervention. Crash data for the year preceding the installation of the devices were compared with data that covered the period of the project.Results: Free-for-use alcohol breath-testing devices were acceptable to and supported by bar staff and people who consumed alcohol in the Kimberley region of Western Australia. Although there was no change in patrons' attitudes to drink- driving and drink-walking during the post-intervention period, there was an increase in the proportion of patrons who walked home with others and a reduction in those who travelled in vehicles as passengers. Indigenous people were less likely to intend driving, were less likely to be driving and were less likely to consider it important to stay under the legal limit when driving. The reverse, however, was true for drink walking. Conclusions: Alcohol breath-testing devices may have a role in rural and remote areas if they are well maintained and supported by education of bar staff and the public as they provide patrons with information about blood-alcohol levels that appears to affect decisions to walk home after consuming alcohol.